Strategi Pengambilan Keputusan Sarana dan Prasarana Kepala Sekolah SDN 01 Pematang Jering Kabupaten Batu Bara - Liani Nasution, Sonya; Sulasmi; Daulay, Isma Hayati; Neliwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The existence of full power or large progressive rights in determining policies to make decisions is limited to the interests of the school principal or those closest to him who are able to influence these decisions. This research uses a qualitative type of research with a qualitative descriptive approach by examining facts that occur in the field. This descriptive qualitative method is used to describe what is true about a symptom, variable or situation. The time this research was conducted was October 10 2023. The location of this research was at SD Negeri 01 Pematang Jering which is located at Jl. Bagan Pematang Jering Village, Sei Suka District, Batu Bara Regency, North Sumatra Province. This research resulted that the Principal's Decision Making Strategy at SD Negeri 01 Pematang Jering Village included identifying problems, drafting decisions, making choices and implementing decisions. Decision Making Style of the Principal of SDN. 01 Pematang Jering Village in Determining School Facilities and Infrastructure. Through the classification of the problems that occur, it can be concluded that the decisions taken by the principal at SD Negeri 01 Pematang Jering Village belong to the type of persuasive decision making style.